2015
DOI: 10.1111/petr.12477
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical cidofovir to treat BK virus‐associated hemorrhagic cystitis in children after hematopoietic stem cell transplantation

Abstract: HC related to BK virus replication might be a severe complication following allogeneic HSCT. There are no clearly defined treatment guidelines in pediatric population. The data on the effectiveness of ICI to manage severe bleeding in children are very limited. We report our experience of intravesical cidofovir in four children, 6-15 yr of age, to manage grade III-IV BK virus-associated HC. Three of four children had high CSA serum level prior to developing cystitis. Intravesical instillations of cidofovir resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…This review additionally identified 13 articles with a total of 219 patients who had received cidofovir therapy for BK-HC in allo-HCT: 195 via intravenous, 19 via intravesical, and 5 via both intravenous and intravesical. Complete response was observed in 60% to 100% of cases, independent of cidofovir dose and administration route [9,11,12,15,17,18,[20][21][22][23][24][25][26].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This review additionally identified 13 articles with a total of 219 patients who had received cidofovir therapy for BK-HC in allo-HCT: 195 via intravenous, 19 via intravesical, and 5 via both intravenous and intravesical. Complete response was observed in 60% to 100% of cases, independent of cidofovir dose and administration route [9,11,12,15,17,18,[20][21][22][23][24][25][26].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cidofovir may be administered intravenously but is associated with potential nephrotoxicity. Intravesical administration has been used to limit systemic toxicity [13,17,18]. The aim of the present retrospective study is to assess the safety profile and efficacy of intravenous and intravesical cidofovir in allo-HCT patients with BK-HC.…”
Section: Introductionmentioning
confidence: 99%
“…Thirteen articles were found that reported use of cidofovir in BKV-HC after allo-HSCT since 2005 [13,[22][23][24][25][26][27][28][29][30][31][32][33]. In total, 219 patients were treated (Table 4): 153 adults and 66 children, with various HC severity grades (grades 1 to 4).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mostly given at 5 mg/kg/week in both primary or secondary pre-emptive therapy for CMV infection with response rates of 50% for CMV disease and 62% to 66% for CMV infection, significant renal toxicities were reported [39]. Several applications of CDF against different viral pathogens in pediatric patients [40] have been reported in recent years, in particular against adenovirus [41], BK virus-associated hemorrhagic cystitis [42,43] and poxvirus [44].…”
Section: Cidofovir (Cdf) -The Last Resortmentioning
confidence: 99%